Parallel voltage sensing in a multiphase converter - Yahaya J.A.; Mansor M.; Yassine R. (Institution of Engineering and Technology, 2023)
Electric inductors; Balancing currents; Equal current distribution; High current applications; Multiphase converters; Parallel-connected; RC networks; Sensing techniques; Voltage sensing; DC-DC converters